Project-based literacy : fun literacy projects for powerful common core learning - Gura, Mark; Gura, Mark (Emerald Publishing Limited : Information Age Publishing, Inc., 2016)
Project-Based Learning; it's a term that most educators have heard and probably have heard good things about, Often, though, they aren't quite sure precisely what its defining characteristics are other than involving students in projects that are supposed to somehow result in their learning things of value.A great many teachers are reluctant to make it part of what they do with their students due to unfounded fears of unrealistic workloads and classroom management issues associated with it. This book should help change that, making the nature of PBL (Project-Based Learning) clear and illustrating how it can be a manageable, effective, and very enjoyable aspect of instruction.The book will present an exciting, alternative approach to literacy instruction that its authors call Project Based Literacy. This will principally be done through the presentation of 20 appealing projects, all of them carefully designed to engage and inspire students (grades 3 - 8) in literacy activities that are both core to the required curriculum and deeply in-synch with the Common Core Standards in English Language Arts. The book will also present support material for this, providing sufficient theory, instructional and classroom management tips, and technology and other 'How To' information to ensure that rank and file classroom teachers can adopt, adapt, and enjoyably and successfully implement the projects and maximize learning in relation to the Common Core Standards for ELA.